Assessment of carrying angle in patients with lateral epicondylitis - Makaju, Sarbada; Palikhe, Pratima; Chaudhary, Sonam; Rai, Chandra Kala (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: The carrying angle is defined as an angle formed in elbow joint when it is fully extended and supinated. The lateral epicondylitis is often known as tennis elbow. It is caused by an overuse injury resulting from excessive load on the extensor tendons at the origin of the extensor carpi radialis brevis (ECRB) tendon. The objective of this study was to determine the carrying angle in lateral epicondylitis patients.Methods: This descriptive study was carried out in the Department of Orthopedics and Physiotherapy in Kathmandu Medical College and Teaching Hospital, between December 15, 2023 to May 16, 2024 after getting the ethical clearance from the Institutional Review Committee. A total of 56 patients with lateral epicondylitis were included. The carrying angle was measured by a manual goniometer by drawing the axes in the arm and forearm. The data was analyzed with Statistical Package for the Social Sciences version 25.0.Results: Lateral epicondylitis was most commonly observed in the right hand (44), out of which 24 were females and 20 males. The lateral epicondylitis was common among the age group 31 to 40 years. The carrying angle in male participants with lateral epicondylitis was mostly between 5° to 10° (20), and in females, it was mostly between 11° to 16° (24).Conclusions: The lateral epicondylitis was more in the right elbow than the left. The carrying angle in the case of the lateral epicondylitis was greater in females than the males. This knowledge will be helpful for the clinician to explain the risk factors, such as ipsilateral rotator cuff tear and nerve entrapment.